A mixed‐effect model approach for assessing land‐based mitigation in integrated assessment models: A regional perspective. (19th July 2021) - Diniz Oliveira, Thais; Brunelle, Thierry; Guenet, Bertrand; Ciais, Philippe; Leblanc, Florian; Guivarch, Céline
Abstract: Given the prospects of low short‐term emissions reduction, carbon removals (CDRs) are expected to play an important role in achieving ambitious mitigation targets in future scenarios of integrated assessment models (IAMs), particularly Bioenergy with Carbon Capture and Storage (BECCS). In this paper, we explore the IAMC 1.5℃ database to depict the characteristics of the two main CDR options present in mitigation scenarios: BECCS and afforestation/reforestation. We apply a linear mixed‐effect model to capture the specific regional and cross‐IAM effects. Results reveal that the distribution of BECCS and afforestation deployment differs across IAMs and regions and, to a second extent, time. BECCS is preferred in the scenarios not for its ability to expand energy use but actually because it appears as an alternative to afforestation, which is associated with a decrease in energy use. However, the regional distribution of CDR deployment does not show a common pattern across scenarios and IAMs. Therefore, a more comprehensive investigation is needed before it can support policy proposals. Abstract : An exploratory study of land‐based mitigation solutions in the IAMC 1.5℃ database under a regional perspective on the role of BECCS and Afforestation. BECCS is preferred in the scenarios not for its ability to expand energy use but actually because it appears as an alternative to Afforestation, which is associated with a decrease in energy use. The regional distribution of CDR deployment does not show a common pattern across scenarios and IAMs. It remains uncertain how much CDR can be delivered and where.